Upskilling for the Modern Workplace: A Case Study on the Most Effective Training Methods and Tools for Bridging the Skills Gap - Buckley, Claudia; Castro Jorge, Maria Fernanda (International Journal of Advanced Corporate Learning (iJAC), 2024)
The skills gap represents a significant challenge in today’s ever-evolving workplace, affecting various industries and age groups. This gap leads to increased recruitment costs, hinders innovation and growth, and reduces productivity and efficiency. Leaders worldwide agree that upskilling is essential for addressing this issue and building a future-ready workforce. However, significant barriers persist, particularly budget constraints and low engagement in training programs. This article presents a case study on a non-profit organization that helps at-risk youth and vulnerable community members develop job readiness skills using the GoSkills course library and learning management system (LMS). Through interviews with the organization's program director and learners, and an analysis of the platform’s reports, the study identifies best practices for upskilling and assesses their effectiveness. The findings provide actionable recommendations for organizations to create a more engaging and effective upskilling strategy without necessarily increasing their training budget.